Advertisement Remove all ads

# Division of Algebraic Expressions - Dividing a Polynomial by a Monomial

Advertisement Remove all ads

# Dividing a Polynomial by a Monomial:

In the case of division of a polynomial by a monomial, we cannot proceed by dividing each term in the dividend polynomial by the divisor polynomial. Instead, we factorise both the polynomials and cancel their common factors.

Let us consider the division of the trinomial 4y3 + 5y2 + 6y by the monomial 2y.

4y3 + 5y2 + 6y = (2 × 2 × y × y × y) + (5 × y × y) + (2 × 3 × y)

We find that 2 × y is common in each term. Therefore, separating 2 × y from each term. We get,

4y3 + 5y2 + 6y = 2 xx y xx (2 xx y xx y) + 2 xx y xx (5/2 xx y) + 2 xx y xx 3.

= 2y (2y^2) + 2y (5/2  y) + 2y(3)

= 2y (2y^2 + 5/2  y +3)    ...(the common factor 2y is shown separately).

Therefore, 4y3 + 5y2 + 6y ÷ 2y

= (4y^3 + 5y^2 + 6y)/(2y)= (2y(2y^2 + 5/2 y + 3))/(2y) = 2y^2 + 5/2 y + 3

Alternatively, we could divide each term of the trinomial by the monomial using the cancellation method.

(4y^3 + 5y^2 + 6y) ÷ 2y = (4y^3 + 5y^2 + 6y)/(2y)

= (4y^3)/(2y) + (5y^2)/(2y) + (6y)/(2y)

 = 2y^2 + 5/2 y + 3

#### Example

Divide 24(x2yz + xy2z + xyz2) by 8xyz using both the methods.

24(x2yz + xy2z + xyz2

= 2 xx 2 xx 2 xx 3 xx[(x xx x xx y xx z) + (x xx y xx y xx z) + (x xx y xx z xx z)]

= 2 xx 2 xx 2 xx 3 xx x xx y xx z  xx ( x + y + z) = 8 xx 3 xx xyz xx (x + y + z) .....(By taking out the common factor)

Therefore,

24(x2yz + xy2z + xyz2) ÷ 8xyz

= (8 xx 3 xx xyz xx (x + y + z))/(8 xx xyz)

= 3 × (x + y + z)

= 3(x + y + z)

Alternately,
24(x2yz + xy2z + xyz2) ÷ 8xyz
= (24x^2yz)/(8xyz) + (24xy^2z)/(8xyz) + (24xyz^2)/(8xyz)
= 3x + 3y + 3z
= 3(x + y + z)
If you would like to contribute notes or other learning material, please submit them using the button below.

### Shaalaa.com

Dividing by monomial long division [00:11:10]
S
##### Series: Dividing a Polynomial by a Monomial
0%

Advertisement Remove all ads
Share
Notifications

View all notifications

Forgot password?